2015
DOI: 10.4111/kju.2015.56.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral stricture formation after ureteroscope treatment of impacted calculi: A prospective study

Abstract: PurposeUrinary calculi is a familiar disease. A well-known complication of endourological treatment for impacted ureteral stones is the formation of ureteral strictures, which has been reported to occur in 14.2% to 24% of cases.Materials and MethodsThis was a prospective study. Ureterotripsy treatment was used on patients with impacted ureteral stones. Then, after 3 months and 6 months, the condition of these patients was assessed by means of a kidney-ureter-bladder (KUB) ultrasound. If the KUB ultrasound indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 11 publications
3
35
0
2
Order By: Relevance
“…A known complication after the treatment of impacted stones is the formation of ureteral strictures. In literature, stricture rates vary from 8 to 24% [ 14 , 24 27 ]. We assume that the reported short-term stricture rate in this study firmly underestimates the long-term stricture rate.…”
Section: Discussionmentioning
confidence: 99%
“…A known complication after the treatment of impacted stones is the formation of ureteral strictures. In literature, stricture rates vary from 8 to 24% [ 14 , 24 27 ]. We assume that the reported short-term stricture rate in this study firmly underestimates the long-term stricture rate.…”
Section: Discussionmentioning
confidence: 99%
“…5 US is reported to occur in 1-4% of patients after ordinary URSL; however, it occurs in 7.8-24% of patients when URSL is performed for impacted stones. 6,7,8 Moreover, there are non-iatrogenic ureteric strictures such as those associated with impacted stones or chronic in ammatory disorders. 9,10 The main purpose of the management of US is to improve hydronephrosis and protect renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative hydronephrosis may be caused by fibrinous exudates produced by the mucosa that precipitate, or fragments of calculi remaining in the ureteral mucosa, causing inflammation and ischemia [ 3 ]. It is reported that the incidence of ureteral stricture formation, as a late complication after URS, occurs in 0% to 4% [ 4 5 ].…”
Section: Introductionmentioning
confidence: 99%